WAYANG DAN FILSAFAT PENDIDIKAN ISLAM - Ahmad Maliki (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2021)
Wayang aside from being a very popular art medium in society, it also has various philosophical meanings, both from the story line, symbols, and tools. In the context of education, puppets have a high contribution in the dissemination of educational values. Referring to its historical perspective, wayang is an educational media aimed at rural communities, through this art approach religious values (Islam) can be well received.Keywords: Philosophy, Wayang, Education